DAMPAK KEBISINGAN DARI AKTIFITAS BANDARA SULTAN THAHA JAMBI TERHADAP PEMUKIMAN SEKITAR BANDARA - Peppy Herawati (Universitas Batanghari Jambi, 2016)
The increasing needs of the people of Jambi on air transport makes Sultan Taha Airport increased airline service. The airport activity is potentially causing the noise. Noise is unwanted sound, causing health problems and human comfort. Around the airport there are still many settlements that could be affected due to the sound emitted from flying activity, causing hearing loss, discomfort and sleep disorders. The purpose of this study was to determine the noise level of flight activity in residential areas and how their impact. Noise measurements carried out for 8 days at which point the first three points are on the road Soekarno Hatta, point II at the South Rim, and the third point in the former area in the village Talang MTQ Jambi Hyacinths by using Sound Level Meter. The measurement results obtained average noise level at the point I is 58.4 dB, point II was 65.5 dB and the third point is 68 dB. It was concluded that the region does not deserve to be a residential area because of the noise that occurs above the threshold quality standard that is 55 dB. This has implications for public health in the vicinity where the 30 respondents showed at the point I feel very noisy 40% and 60% is quite noisy, and point II approximately 10% feel very noisy and the remaining 90% is quite noisy. So is the case with settlements in point III about 10% feel very noisy and 90% quite noisy. for residential health disorders found about 60% of respondents experienced sleep disturbances, hearing loss due to noise exposure is too long. key words: noise, health impact, airport,